2007
DOI: 10.1088/0022-3727/40/7/030
|View full text |Cite
|
Sign up to set email alerts
|

A new design of a bright cascaded arc light source: measurements and simulations

Abstract: Profiling the arc channel of a cascaded arc into an hourglass-like shape results in an extremely high light output intensity (3.5 × 1012 Wm−2 m−1 sr−1 in the near-infrared) at an input power of 2.2 kW, a good stability (better than 5 × 10−4) and a small solid angle of the emitted light beam (Ω = 0.015 sr). These optical properties are advantageous for spectroscopic applications that require a high light intensity over a broad wavelength range in a small solid angle. The absolute light output is measured and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The arc, which generates an expanding thermal plasma, consists of a stack of four water‐cooled copper plates with a central bore of 4 mm in diameter and has a total length of 24 mm (Figure 1). 5, 6 The electrically floating plates are insulated from each other by PVC spacers 35. The head of the arc contains three tungsten cathodes and the gas injection port.…”
Section: Methodsmentioning
confidence: 99%
“…The arc, which generates an expanding thermal plasma, consists of a stack of four water‐cooled copper plates with a central bore of 4 mm in diameter and has a total length of 24 mm (Figure 1). 5, 6 The electrically floating plates are insulated from each other by PVC spacers 35. The head of the arc contains three tungsten cathodes and the gas injection port.…”
Section: Methodsmentioning
confidence: 99%
“…ε HFS is the surface IR emissivity and σ is the Stefan-Boltzmann constant. q other refers to heat disturbances other than conduction, convection, and thermal radiation, such as heat loads induced by light [24], ion fluxes [14], or molecular fluxes [23] from the plasma source.…”
Section: Dhfsmentioning
confidence: 99%
“…In this ideal situation, we can extract the radical recombination heat loads using equation (4). It has been reported that the heat loads from the plasma source are radially symmetric with respect to the center of the nozzle, and they do not have homogeneous spatial distributions over the size of the DHFS [14,23,24]. Therefore, to reach the ideal situation, we aligned the DHFS to the center of the plasma source, as shown in figure 5.…”
Section: Profile Of the Radical Recombination Heat Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burm et al proposed an arc with a varying channel diameter to locally enhance the electron density to enhance the radical yield of a flowing arc [13][14][15][16]. In the present work, we will make a numerical analysis of the behaviour of a stationary arc, in which a constricted channel is used to enhance the local electron density and light emission, as proposed in [17,18]. In order to increase the accuracy of the modelling, accurate and recent cross sections for the various elastic and inelastic processes are used.…”
Section: Introductionmentioning
confidence: 99%